Disease stage determines the efficacy of treatment of a paediatric neurodegenerative disease. (10th April 2014) - Hassiotis, Sofia; Beard, Helen; Luck, Amanda; Trim, Paul J.; King, Barbara; Snel, Marten F.; Hopwood, John J.; Hemsley, Kim M.
Abstract Lysosomal storage disorders are a large group of inherited metabolic conditions resulting from the deficiency of proteins involved in lysosomal catabolism, with resulting accumulation of substrates inside the cell. Two‐thirds of these disorders are associated with a neurodegenerative phenotype and, although few therapeutic options are available to patients at present, clinical trials of several treatments including lysosomal enzyme replacement are underway. Although animal studies indicate the efficacy of pre‐symptomatic treatment, it is largely unknown whether symptomatic disease‐related pathology and functional deficits are reversible. To begin to address this, we used a naturally‐occurring mouse model with Sanfilippo syndrome (mucopolysaccharidosis type IIIA) to examine the effectiveness of intracisternal cerebrospinal fluid enzyme replacement in early, mid‐ and symptomatic disease stage mice. We observed a disease‐stage‐dependent treatment effect, with the most significant reductions in primary and secondary substrate accumulation, astrogliosis and protein aggregate accumulation seen in mucopolysaccharidosis type IIIA mice treated very early in the disease course. Affected mice treated at a symptomatic age exhibited little change in these neuropathological markers in the time‐frame of the study. Microgliosis was refractory to treatment regardless of the age at which treatment was instigated. Although longer‐term studies are warranted, these findings indicate the importance of early intervention in this condition.